EFEKTIVITAS PENERAPAN SIASN TERHADAP KUALITAS PELAYANAN ADMINISTRASI KEPEGAWAIAN DI BADAN KEPEGAWAIAN DAN PENGEMBANGAN SUMBER DAYA MANUSIA KABUPATEN SUMBAWA BARAT - FAKHRUDDIN, ERWIN; UMAR, UMAR; YULIADI, IMAM (Universitas Mahasaraswati K. Mataram, 2023)
The purpose of this research is to describe the implementation of the Civil Servant Information System (SIASN) innovation in improving the quality of administrative personnel services and to analyze the effectiveness of the implementation of the Civil Servant Information System (SIASN) innovation on the quality of administrative personnel services in the Badan Kepegawaian dan Pengembangan Sumber Daya Manusia (BKPSDM) Kabupaten Sumbawa Barat. The research findings show that the implementation of the Civil Servant Information System (SIASN) innovation in the BKPSDM Kabupaten Sumbawa Barat has been successful, resulting in an improvement in the quality of administrative personnel services. This improvement includes increased efficiency, transparency, and accuracy in administrative personnel matters.Regarding the effectiveness of the SIASN implementation at the BKPSDM Kabupaten Sumbawa Barat, it can be evaluated based on the indicators of Easier, Better, Faster, Cheaper, and Safety. In general, the effectiveness is considered